MAKNA FILOSOFIS MADU KULAU DALAM PROSESI UPACARA PERKAWINAN ADAT SERAWAI DI KABUPATEN BENGKULU SELATAN - Irwan irwan (Manthiq, 2017)
Abstract: The philosophical meaning of “Madu Kulau” in the procession of Ceremonial Ceremony of Adat Serawai  in South  Bengkulu  Regency  can  be  concluded by the  Chairman of the  committee (tuau  kerjau) facing  the  adat  leader by bringing  forth  while  applying  for permission to  the  adat  chief.  After applying for permission to the  village head,  the  committee chairman (tuau  kerjau) faces  the  head of the  group from the  men  (tuau  mendah) by unifying the  two livers. Then convey  the  intent  and  purpose that will be deliberate to determine where the residence and place  of business for the bride after the marriage contract is implemented. Immediately mentions selected and  pre-determined gifts in honey  rasan  (musyawarah)10 days  before  the  wedding procession is held.  Chairman of the  entourage (old  mendah) responded to the  rasan  called  by the  chairman of the  committee by agreeing to the  selected rasan.  After determining the features selected by the women’s family. The chairman of the committee (seniu  kerjau) returns  to the village head to present his langguwai  again while giving the envelope containing the money  requirement for the traditional  chairman inaugurated the selected rasan  in honey  kulau.  The adat  chairman announces in front of the people present about  the agreement agreed upon  by both parties  and inaugurated it. Then the procession of honey I closed with prayer of salvation for the groom, family and audience to get the salvation from God’s grace.